A Document Review of the Al-Qur'an Hadith Curriculum in Madrasah Tsanawiyah: An Analysis of Learning Objectives, Materials, and Evaluation - Alfia Fina Shabira; Irawati Irawati; Saiful Arif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study conducted a systematic review of curriculum documents for the Al-Qur'an and Hadith subject in madrasahs in the context of the implementation of the Merdeka Curriculum, by comprehensively examining the relationship between learning objectives, content, and assessment strategies. Using a documentation-based qualitative approach, this study analyzed Learning Objectives (LO), Learning Objective Sequences (LOS), and teaching modules as primary data sources. The results of the analysis reveal that the curriculum objectives have been systematically and structurally formulated through the integrated incorporation of cognitive, affective, and psychomotor competencies across all domains of learning. The learning content centers on three fundamental domains tajwid, the content of the Qur’an, and hadith studies which are delivered through contextual learning experiences and activities oriented toward real-world practice. Assessment practices emphasize authentic assessment as a tool to measure students’ abilities not only in reading, memorizing, and understanding but also in consistently applying and actualizing Islamic values in their daily lives. These findings affirm that the Qur’an and Hadith curriculum within the framework of the Merdeka Curriculum makes a significant contribution to the holistic strengthening of students’ religious character.